Determining Subscribers’ Attitude towards and Satisfaction from Airtel and Citycell: An Empirical Assessment of the Martin Fishbein Multiattribute Model - Anwar Pasha, Syed Habib; Masoom, Muhammad Rehan (Indian Journal of Marketing, 2012)
This study was conducted to compare attitude and satisfaction of Airtel and Citycell subscribers based on Martin Fishbein Multiattribute Model. Two hundred twenty respondents from six divisions of Bangladesh were interviewed to collect their opinion. The findings show that subscribers of Airtel hold more favorable attitude and higher satisfaction level in comparison to Citycell subscribers. It has been found that low call rate, good network coverage, pulse facility, connected with land phone and friends & family’s number are the most influential factors to choose particular company’s mobile connection. The outcome of this study might be used to develop the framework in order to achieve higher customer satisfaction and to use and incorporate factors in their offerings, which are mostly dominant to influence customers in case of purchasing decision.